The camera's abstractions and "the" truth - Galante, Peter, author; Dormer, James T., advisor; Orman, Jack L., committee member; Zoellner, Robert, committee member (Colorado State University. Libraries, 1987)
It must be some law of nature that Existentialists are to be reared in urban environments. I suppose it is the obvious disconnection from the earth in the cities' concrete canyons that emphasizes existential alienation. In places like New York, distinctions of nature are blurred, as it is always night in the subway, and it is always day in the streets, under the glare of unnatural light, even if the sun is shining. To reduce the city to its fundamental unit, I would say that the city is made entirely of walls. I'm sure this contradicts the majority opinion that the city is made of people, but I just don't "see" them. I only see the walls and how the city's unique light plays on them. Emerson, an unlikely Existentialist said correctly, "Every wall is a door." As walls define our existence, let us look for the door and the way out only in our personal walls. My earliest memories are of television, of a large mahogany veneer set, with its horizontally ovoid picture. The images I recall are not of the children's programs of the fifties, but the "film noir" genre movies of the forties, which dominated WPIX's weekend schedule. Dark empty streets with a hardened, solitary detective struggling to correct some injustice. The image is very clear to me, but by the time the filmed original was reproduced by our television, it was reduced to a fuzzy, high contrast abstraction. The highlights became a green white glow and the shadows became murky and indiscriminate. This effect, a consequence of early television's technical limitations, heightened the sense of drama as it facilitated a willful suspension of reality. Throughout this decade when, as a child, I was forming my impression of the world, camera images began to dominate the world's access to visual media. Thereafter, the camera's inherent abstraction was understood to be a faithful duplication of "reality" and was therefore perceived as "the" truth. Therein, mechanical rather than interpretive means gave man the look of things and, more important, his outlook on them. It is for these reasons I find it necessary to search for fundamental meanings and human equivalents against walls which reference a time before the camera's influence, with the very instrument which induced a changed perception of society. It is necessary for me to work with our culture's primary visual medium in order to understand its power over the traditions it consumed. Traditionally, art has used material means to gain spiritual ends. The traditions of Renaissance printmaking provide a conceptual foundation, without which my use of the camera image would be as empty as the pervasive media images. I do not accept the camera's view, de facto, as truth in the manner which society nostalgically accepts the mechanical likenesses in the family picture album. Nor do I attempt to manipulate the image in a surrealist or dada fashion simply to create shocking juxtapositions or anti-art sentiments. I work simply and directly with traditional printmaking techniques to heighten visual and emotional impact. In this way I attempt to strike a balance between the unsettling impact of technology and the stability inherent in the spiritual dimensions of tradition. For me neither the camera nor the processes of printmaking are reproductive techniques, but, rather, are investigative tools with almost mythic significance. For all the technology in the world, there is nothing quite like the odors and effort of mixing bone, vine and burnt oil in handmade ink to awaken the mythic sense of tradition. In this age, artists are finding that to make something new they need to borrow from the old. To understand the present you need to have an understanding of the past. This is my story of how I began to remember. This is why I continue to work.
Keywords: Photography, Artistic